We should not be friends : the story of a friendship - Schwalbe, Will (Alfred A. Knopf, 2023)
"From the author of the best-selling and beloved The End of Your Life Book Club-a new book that tracks an improbable and life-changing college friendship over the course of forty years. Author Will Schwalbe describes his friendship with unlikely college-buddy Maxey through marriage, divorce, and career changes up until the present day, noting what makes their bond so special and enduring"--